A combined use of Panax ginseng extract and the probiotic, Lactobacillus plantarum in the diet of Asian seabass, Lates calcarifer: Effects on growth, immunity and survival after bacterial challenge - Xiaojie Hou; Jianfeng Zhang; Neda Behmagham; Hamed Ghafarifarsani (Aquaculture Reports)
This study evaluated the effects of the probiotic Lactobacillus plantarum (LAC-P) and powdered Panax ginseng extract (GINS) on the growth, immunity, and survival of Asian seabass (Lates calcarifer) following a Streptococcus iniae infection. Eight groups were tested: control, LAC-P (1 × 1010 CFU L. plantarum /100 g diet), varying doses of GINS (0.1 %, 0.5 %, 1 %), and combinations of LAC-P with these doses of GINS. All experiments were carried out in three replicates and fish (Mean weight: 25.3 ± 4.2 g) of all treatments fed for 60 days. After this feeding period, a challenge test was also done with Streptococcus iniae over 14 days. The growth performance and digestive enzyme activities (trypsin, chymotrypsin, lipase) significantly improved in fish supplemented with LAC-P and LAC-P + GINS (0.1–1 %) (P < 0.01). The treatment, LAC-P + GINS (1 %) showed highest performance, as a final weight, weight gain, specific growth rate and feed conversion ratio of 81.4 ± 4.1 g, 223.6 ± 7.3 %, 1.94 ± 0.07 % and 1.1 ± 0.02 respectively obtained for this treatment (P < 0.01). This treatment also showed highest digestive enzyme activities for trypsin (5.2 ± 0.11 U/mg protein), chymotrypsin (3.9 ± 0.15 U/mg protein) and lipase (2.12 ± 0.04 U/mg protein) (P < 0.01). The intestinal lactic acid bacteria with maximum load of 4.1 ± 0.5, 3.9 ± 0.5 and 3.6 ± 0.4 log CFU/g intestine at LAC-P + GINS treatments, increased, following the probiotic administration, while total bacterial count remained unchanged (P < 0.01). The antioxidant enzyme activities in blood significantly increased in response to LAC-P, GINS (0.5–1 %) and their combinations compared to control (P < 0.01). The highest activity of Superoxide dismutase (5.44 ± 0.62 U/mg), catalase (15.68 ± 1.04 U/mg) and glutathione peroxidase (14.5 ± 2.4 U/mg) was observed in LAC-P + GINS (1 %) treatment (P < 0.01). Also, LAC-P and GINS alone and their combinations enhanced total antioxidant capacity (T-AOC), with highest-value for fish of LAC-P + GINS (1 %) (0.4 ± 0.05 U/mg protein) and LAC-P + GINS (0.5 %) (0.34 ± 0.04 U/mg protein) (P < 0.01). The immune components of serum [total immunoglobulin (Ig), lysozyme (lyz), alternative complement activity (ACH50), myeloperoxidase (MPO), nitroblue tetrazolium (NBT), total protein] and mucus [protease, Ig, alkaline phosphatase (ALP), Lyz] were mostly elevated in fish supplemented with LAC-P, GINS (1 %) and LAC-P + GINS (0.1–1 %) (P < 0.01). The maximum elevations of immune components of serum (Ig: 6.5 ± 0.4 mg/ml, lyz: 180.6 ± 6.8 U/ml), ACH50: 60.2 ± 5.06 U/ml, MPO: 4.24 ± 0.19 OD at 450 nm, NBT: 0.4.6 ± 0.03 OD at 620 nm and total protein: 4.1 ± 0.22 g/dl) and mucus (protease: 16.2 ± 2.4 U/ml, alkaline phosphatase: 4.9 ± 0.3 U/ml, Ig: 2.37 ± 0.2 mg/ml, lyz: 101.4 ± 5.09 U/ml) mostly were for LAC-P + GINS (1 %) treatment (P < 0.01). Supplementation of fish with GINS alone or combined with LAC-P significantly mitigated oxidative stress, as malondialdehyde (MDA) levels decreased in these treatments (P < 0.01). The most reductions in MDA (17.3 ± 2.1 nmol/L) observed in the LAC-P + GINS (1 %) treatment (P < 0.01). After bacterial challenge, fish fed supplementation with GINS (0.5 %), GINS (1 %) and LAC-P + GINS (0.1–1 %) showed lower mortality rate (P < 0.01). LAC-P + GINS (1 %) treatment showed the lowest (35.2 ± 4.5 %) fish mortality (P < 0.01). In conclusion, fish supplemented with LAC-P and GINS, especially at 1 % level, showed significant improvements in growth, digestive enzyme activities, antioxidant enzyme levels, and immune responses. The combination of LAC-P and GINS (1 %) resulted in the lowest mortality rate and best overall performance, demonstrating their potential for enhancing fish immunity against the bacterial challenge.